2020
DOI: 10.1097/tp.0000000000003593
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Profile and Outcome of COVID-19 in 250 Kidney Transplant Recipients: A Multicenter Cohort Study From India

Abstract: Background. There is a scarcity of data on the consequences of coronavirus disease-19 (COVID-19) infections in kidney transplant recipients (KTRs) from emerging countries. Methods. Here, we present a cohort study of 13 transplant centers in India including 250 KTR (226 living and 24 deceased donors) with polymerase chain reaction-confirmed COVID-19 positivity from March 23, 2020, until September 15, 2020. We detailed demographics, immunosuppression regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

18
101
2
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 95 publications
(130 citation statements)
references
References 35 publications
18
101
2
9
Order By: Relevance
“…Although the median age of the patients appears slightly lower than in other reports, the overall patient profile in terms of comorbidities and sex distribution appears to be similar to other reports (Felldin et al, 2021;Lubetzky et al, 2020). The overall outcomes of this first Eastern European cohort of transplant patients are comparable to those of patients in other single-centre reports or registry analyses, and this further suggests the existence of yet unidentified risk factors particular to this patient group (Caillard et al, 2020;Felldin et al, 2021;Hoek et al, 2020;Hillbrands et al, 2020;Kute et al, 2020;Nair et al, 2020).…”
Section: Discussionsupporting
confidence: 79%
“…Although the median age of the patients appears slightly lower than in other reports, the overall patient profile in terms of comorbidities and sex distribution appears to be similar to other reports (Felldin et al, 2021;Lubetzky et al, 2020). The overall outcomes of this first Eastern European cohort of transplant patients are comparable to those of patients in other single-centre reports or registry analyses, and this further suggests the existence of yet unidentified risk factors particular to this patient group (Caillard et al, 2020;Felldin et al, 2021;Hoek et al, 2020;Hillbrands et al, 2020;Kute et al, 2020;Nair et al, 2020).…”
Section: Discussionsupporting
confidence: 79%
“…11 Studies from Spain and India reported a similar incidence of AKI in kidney transplant recipients with COVID-19 (47% and 48%, respectively). 7,9 Favà et al reported that AKI stage 3 was associated with increased mortality, but no patients had acute graft rejection during a 2-week follow-up period. 9 In contrast, Kute et al reported 4.8% graft loss after 28-day follow-up, which occurred in patients with baseline chronic kidney disease.…”
Section: Discussionmentioning
confidence: 99%
“…9 In contrast, Kute et al reported 4.8% graft loss after 28-day follow-up, which occurred in patients with baseline chronic kidney disease. 7 Interestingly, 20 patients screened positive for donor-specific antibodies, of which 10 had de novo antibodies-this was thought to be related to reduced immunosuppression during COVID-19 treatment. 7 Risk factors associated with kidney transplant recipients' mortality include age, [7][8][9][10][11] disease severity, dyspnea, and ARDS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations